Pengembangan Website Mekanisme Pengelolaan Donasi - Arwin Halim; William William; Rin Rin Meilani Salim (Jurnal SIFO Mikroskil, 2018)
Magabudhi and Patria are Buddhist Religious Organizations in North Sumatra province. These two organizations often conduct social activities where this activity can be carried out with the support of donations from sympathizers and donors. Both of them do not have formal procedures for donations management that make them experienced difficulties to socialize, fundraising, manage donations, and report the collected donation to donors. Meanwhile, the management of event are depended by the committee who has an experience before. The reporting of activities is published through internal notice boards and not be updated properly in online media. Therefore, Donacius was developed by having a formal procedure for the mechanism of donation management and as a medium for publication, fundraising, management of donations and reporting of social activities. Donacius was developed not only for the use of these two organizations, but Donacius can be used by many organizations. Others organization can register at Donacius to raise funds and donors can donate to many organizations through Donacius. With the presence of Donacius, it will increase the accountability and transparency of social activities of the organization to increase donor trust.